Restoration of the pastureland ecosystem in Western Inner Mongolia - Liu, Heng; Leihua, Geng; Zhijun, Yan; Huaping, Zhong; Cai, Ximing (American Society of Civil Engineers, 2003)
One of 410 papers presented at the World Water & Environmental Resources Congress held in Philadelphia, PA June 23-26, 2003. The objective of the Congress is to advance communication amongst water and environmental professionals and to provide an avenue to demonstrate the latest technological advances in respective fields.